2007
DOI: 10.1021/jf0724670
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Ice Crystal Growth in Ice Cream Mix by Gelatin Hydrolysate

Abstract: The inhibition of ice crystal growth in ice cream mix by gelatin hydrolysate produced by papain action was studied. The ice crystal growth was monitored by thermal cycling between -14 and -12°C at a rate of one cycle per 3 min. It is shown that the hydrolysate fraction containing peptides in the molecular weight range of about 2000 -5000 Da exhibited the highest inhibitory activity on ice crystal growth in ice cream mix, whereas fractions containing peptides greater than 7000 Da did not inhibit ice crystal gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(95 citation statements)
references
References 47 publications
3
90
0
2
Order By: Relevance
“…Gelatin hydrolysate (small peptides, 2000-5000 kDa) produced by papain action showed inhibitory activity on ice crystal growth in ice cream mix (Damodaran, 2007). More studies are required to explore the possibility of special processing (e.g., enzymatic reaction) on safety and nutritional capacity of convenient food products, such as milk and meat, as new sources of ISPs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gelatin hydrolysate (small peptides, 2000-5000 kDa) produced by papain action showed inhibitory activity on ice crystal growth in ice cream mix (Damodaran, 2007). More studies are required to explore the possibility of special processing (e.g., enzymatic reaction) on safety and nutritional capacity of convenient food products, such as milk and meat, as new sources of ISPs.…”
Section: Resultsmentioning
confidence: 99%
“…In this model, nonpolar side chains of amino acids (e.g., methyl groups) fit in regular spacing on the surface of ice, i.e., ice cages, grooves, or hexagonal rings, through favorable van der Waals and/or hydrophobic interactions (Jorov et al, 2004;Yang et al, 1998). Hydrogen bonds may support these contacts; i.e., Damodaran (2007) proposed that formation of hydrogen bonds between an ice crystal and gelatin hydrolysate is inhibiting ice crystal growth. However, hydrogen bonding is not necessarily essential for ice binding.…”
Section: Mechanisms Of Action Of Ispsmentioning
confidence: 99%
“…34 Similarly, novel ingredients are being suggested to help control ice recrystallization, among them are the antifreeze proteins that can be extracted from natural sources 36 and the use of gelatin hydrolyzates. 37 Recently, Hagiwara et al 38 indicated that the self-diffusion coefficient of water in a freezeconcentrated matrix is a useful parameter for predicting and controlling the recrystallization rate.…”
Section: Ice Crystal Size and Morphology In Ice Creammentioning
confidence: 99%
“…Furthermore, in a series of studies Damodaran investigated the potential of using gelatin hydrolysed derivatives as ice crystal growth controllers in ice cream systems. Gelatin hydrolysed derivatives with molecular weights of 2000 -5000 Da have shown outstanding ability to hinder ice recrystallisation in ice cream (Damodaran, 2007). The recrystallisation inhibitory activity of gelatin hydrolysates is not observed in larger fractions (> 7000 Da).…”
Section: The Use Of Isp In Ice Creammentioning
confidence: 99%
“…Damodaran attributed the antifreeze activity of gelatin hydrolysates to the formation of an oxygen triad plane at the C-terminal with oxygen-oxygen distances similar to those found in ice nuclei. The presence of this oxygen triad plane facilitates the binding via hydrogen bonds with the prism face of ice nuclei hindering the ice crystal growth in the ice cream mix (Damodaran, 2007;Wang and Damodaran, 2009) reported that the use of cationic polypeptide fractions (700 -1400 Da) derived by papain gelatin hydrolysis at 30 -37 °C , pH = 7 in ice cream mixes subjected to a freeze-thaw protocol (between -10 and -12 °C) reduced the ice recrystallisation rate by a factor of ten.…”
Section: The Use Of Isp In Ice Creammentioning
confidence: 99%